Committed Human CD23-Negative Light-Zone Germinal Center B Cells Delineate Transcriptional Program Supporting Plasma Cell Differentiation - Santamaria, Kathleen; Desmots, Fabienne; Leonard, Simon; Caron, Gersende; Haas, Marion; Delaloy, Céline; Chatonnet, Fabrice; Rossille, Delphine; Pignarre, Amandine; Monvoisin, Céline; Seffals, Marine; Lamaison, Claire; et al. (Frontiers in Immunology, 2021)
B cell affinity maturation occurs in the germinal center (GC). Light-zone (LZ) GC B cells (BGC-cells) interact with follicular dendritic cells (FDCs) and compete for the limited, sequential help from T follicular helper cells needed to escape from apoptosis and complete their differentiation. The highest-affinity LZ BGC-cells enter the cell cycle and differentiate into PCs, following a dramatic epigenetic reorganization that induces transcriptome changes in general and the expression of the PRDM1 gene in particular. Human PC precursors are characterized by the loss of IL-4/STAT6 signaling and the absence of CD23 expression. Here, we studied the fate of human LZ BGC-cells as a function of their CD23 expression. We first showed that CD23 expression was restricted to the GC LZ, where it was primarily expressed by FDCs; less than 10% of tonsil LZ BGC-cells were positive. Sorted LZ BGC-cells left in culture and stimulated upregulated CD23 expression but were unable to differentiate into PCs – in contrast to cells that did not upregulate CD23 expression. An in-depth analysis (including single-cell gene expression) showed that stimulated CD23-negative LZ BGC-cells differentiated into plasmablasts and time course of gene expression changes delineates the transcriptional program that sustains PC differentiation. In particular, we identified a B cell proliferation signature supported by a transient MYC gene expression. Overall, the CD23 marker might be of value in answering questions about the differentiation of normal BGC-cells and allowed us to propose an instructive LZ BGC-cells maturation and fate model.